Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee. (1st June 2023) - Xu, Canhua; Lu, Jiaming; Zeng, Qingzhu; Zhang, Junjia; Dong, Lihong; Huang, Fei; Shen, Yingbin; Su, Dongxiao
Highlights: Magnetic Nanometer combined with Microwave Thawing (MN-MT) is a rapid thawing treatment. The release of phenolic compounds in frozen lychee was promoted by MN-MT. MN-MT protected thermally unstable compound procyanidin B2 from degradation. Abstract: Magnetic nanometer combined with microwave thawing (MN-MT) could become a novel solution to challenges uneven and overheating of microwave thawing (MT), while retaining high thawing efficiency, compared to conventional water immersion thawing (WT). In this study, MN-MT was applied to thaw fruit (lychee as an example) for the first time, and was evaluated by comparison with WT, MT and water immersion combined with microwave thawing (WI-MT). Results showed that MN-MT could significantly shorten the thawing time of frozen lychee by 80.67%, 25.86% and 18.83% compared to WT, MT and WI-MT, respectively. Compared to WT, MN-MT was the only thawing treatment which significantly enhanced the release of quercetin-3- O -rutinose-7- O -α-l -rhamnoside, according to HPLC-DAD. Meanwhile, thermal-sensitive procyanidin B2, phenylpropionic acid and protocatechuic acid were found to be protected from degradations only by MN-MT based on UPLC-ESI-QTOF-MS/MS results. In summary, MN-MT is a potential novel treatment for rapid thawing and quality maintenance of frozen fruits.